The Effect of Psilocin on Memory Acquisition, Retrieval, and Consolidation in the Rat - Rambousek, Lukas; Palenicek, Tomas; Vales, Karel; Stuchlik, Ales (Frontiers in Behavioral Neuroscience, 2014)
The involvement of the serotonin system in the pathophysiology of schizophrenia has been elucidated by experiments with hallucinogens. Application of a hallucinogen to humans leads to changes in perception, cognition, emotions and induction of psychotic-like symptoms that resemble symptoms of schizophrenia. In rodent studies, their acute administration affects sensorimotor gating, locomotor activity, social behavior and cognition including working memory, the phenotypes are considered as an animal model of schizophrenia. The complexity and singularity of human cognition raises questions about the validity of animal models utilizing agonists of 5-HT2A receptors. The present study thus investigated the effect of psilocin on memory acquisition, reinforced retrieval and memory consolidation in rats. Psilocin is a main metabolite of psilocybin acting as an agonist at 5-HT2A receptors with a contribution of 5-HT2C and 5-HT1A receptors. First, we tested the effect of psilocin on the acquisition of a Carousel maze, a spatial task requiring navigation using distal cues, attention and cognitive coordination. Psilocin significantly impaired the acquisition of the Carousel Maze at both doses (1 and 4 mg/kg). The higher dose of psilocin blocked the learning processes even in an additional session when the rats received only saline. Next, we examined the effect of psilocin on reinforced retrieval and consolidation in the Morris water maze (MWM). The dose of 4 mg/kg disrupted reinforced retrieval in the Morris water maze. However, the application of a lower dose was without any significant effect. Finally, neither the low nor high dose of psilocin injected post-training caused a deficit in memory consolidation in the MWM. Taken together, the psilocin dose dependently impaired the acquisition of the Carousel maze and reinforced retrieval in MWM; however, it had no effect on memory consolidation.